Pertimbangan Usia dalam Penerapan Sanksi Terhadap Anak Pelaku Kejahatan Berat - Putri Sindi Rola; Elly Sudarti; Erwin Erwin (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
Juvenile delinquency is a problem. Children who receive insufficient attention tend to commit criminal acts, ranging from theft to serious violence, which harm both themselves and society. Indonesia’s juvenile justice system emphasizes protection and rehabilitation, particularly for children under 14 who can only be subjected to non-penal measures, while children aged 14–17 undergo diversion processes and juvenile court proceedings. Nevertheless, serious crimes create tension between child protection and the demands for justice for victims. Sentencing of children must consider age, the severity of the offense, and ethical legal principles, including preventive, retributive, and reformative objectives. This study employs normative legal research using statutory and case approaches to analyze the implications of a child’s age on the type and form of sanctions. The results highlight that age significantly influences sanction application, ensuring justice while encouraging children to improve themselves and develop optimally.